2022
DOI: 10.1155/2022/3732243
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and Safety of Endoscopic Tympanic Membrane Catheterization Plus Ofloxacin Ear Drops in the Treatment of Secretory Otitis Media in Infants and Toddlers

Abstract: Objective. To investigate the efficacy and safety of endoscopic tympanic membrane catheterization and ofloxacin ear drops in the treatment of secretory otitis media in infants and toddlers. Methods. A total of 80 children suffering from secretory otitis media who underwent treatment in our hospital from July 2018 to April 2020 were divided into the control group (n = 40) and experimental group (n = 40) by randomization. The control group was treated with endoscopic tympanic membrane catheterization alone, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%